History of pollutant adjuvants in respiratory allergy - Shusterman, Dennis (Frontiers in Allergy, 2024)
Combined exposures to allergens and air pollutants emerged as a topic of concern in scientific circles by the 1980's, when it became clear that parallel increases in respiratory allergies and traffic-related air pollution had been occurring during the 20 th century (1,2). Although historically there has been a tendency to treat exposure-related symptoms as either allergic or toxicologic in nature, crossinteractions have since been established between the two modalities. For example, exposure to selected air pollutants in concert with a given allergen can increase the likelihood that an individual will become sensitized to that allergen, strongly suggesting that the pollutant acted as an adjuvant.Although not a review of underlying mechanisms, the purpose of this mini-review is to highlight the potential significance of co-exposure to adjuvant chemicals in predicting allergic sensitization in the respiratory tract. The current discussion emphasizes the upper airway as a model for respiratory challenge studies, the results of which may be applicable -not only to allergic rhinitis -but also to conjunctivitis and asthma.